On the distribution of the distorted Euler function - Kalinka, V.; Postnikova, L. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Калинка, Л. П. Постникова. О распределении значений испорченной функции Эйлера V. Kalinka, L. Postnikova. Deformuotos Eilerio funkcijos reikšmių pasiskirstymo klausimu